Robust optical tracking of individual ejecta particles in hypervelocity impact experiments. (2nd October 2017) - Gulde, Max; Kortmann, Lukas; Ebert, Matthias; Watson, Erkai; Wilk, Jakob; Schäfer, Frank
Abstract: New insights into the kinematics of ejecta clouds and the dynamics of crater formation are gained from the introduction of an approach to track individual particles ejected from a horizontal hypervelocity impact of a 2 mm aluminum sphere at 6.3 km s −1 into vertically aligned Carrara marble. Particle trajectories are determined with 500 ns temporal resolution inside a 1–2 mm thick laser light sheet illuminating a single plane within the ejecta plume. In contrast to optical flow analysis, the methodology presented here enables us to track individual particles instead of relying on field‐averaged information. This is realized by correlating particles not via their geometric shape but through their trajectory directly. It robustly identifies even partially obscured or strongly tumbling particles, allowing for a comprehensive physical description of the highly dynamical excavation process based on the precise determination of position, time, and ejection velocity of each individual particle. Specifically, we find ejecta particles launched in a short window of about 0–25 μs after impact and up to a radial distance of 10 mm from the impact location. During this time interval, the transient crater radius grows from 2 ± 1 mm to 6 ± 2 mm. Velocities between 70 m s −1 and 1 km s −1 are observed and reveal a substantial steepening of the ejecta curtain within 15 μs after the impact. We additionally determine the particle size and find a μ‐parameter of 0.6 for Carrara marble which is consistent with theoretical predictions for nonporous materials.